Development of rapid low temperature assistant modified QuEChERS method for simultaneous determination of 107 pesticides and relevant metabolites in animal lipid. (30th November 2022) - Zhao, Huiyu; Zhao, Zhenni; Li, Xue; Di, Shanshan; Qi, Peipei; Wang, Zhiwei; Wang, Jiao; Tian, Pei; Xu, Hao; Wang, Xinquan
Highlights: An analytical method for 107 pesticides in four animal lipid was developed. The approach enables the pesticide analysis with a wide range of lipophilicity. A rapid low temperature assistant QuEChERS method was used for fat clean up. The clean up mechanism using different sorbents were studied in detail. Abstract: A modified QuEChERS LC-MS/MS method was developed for 107 pesticides analysis in animal lipids such as pork lard, mutton tallow, chicken oil and butter. The challenges for high fat matrices clean up were studied in details by optimizing dispersive purification adsorbents coupled with rapid low temperature assistant methods. The method validation was carried out using pork lard and further appplied to other matrices by testing their recoveries. Good linearities were obtained with correlation coefficients greater than 0.99. Sensitive LOQs ranged from 5.0–50.0 μg kg −1 . Both inter-day and intra-day precisions were lower than 20% indicating the good precision and accuracy of this method. The method applied to four animal lipids with 93%∼100% of analytes revealed satisfactory recoveries (ranged from 70% to 120%) and RSD (≤20%) at 10 µg kg −1 and 50 µg kg −1 spiking levels respectively related to the matrix.